ADDIE MODEL: PENGEMBANGAN MEDIA LIKURDIN PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Nanda Nitami; Nazliati Nazliati; Rita Sari (FISIP Universitas Malikussaleh, 2023)
Islamic cultural history is one of the subjects that is considered boring. Using media can be an alternative to help the learning process to be more enjoyable. Likurdin is the media that modified the form of monopoly and the History of Khulafaurrasyidin. Developing this media aims to produce learning media on Khulafaurrasyidin History material and determine Likurdin media's effectiveness. This research uses the R&D (Research and Development) method with the ADDIE development model developed by Dick and Carry (1996) with 5 (five) stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques through media expert validator sheets, material experts, and student questionnaire sheets. Based on the results of the study, after being validated by validators from 2 teams of experts, namely media experts at 96% and material experts at 100%, which means that Likurdin learning media is